Government Measures to Promote New Retrofitting Business and Financing Option in Indonesia - Nasip, Ismiriati; Sudarmaji, Eka (International Journal of Engineering and Technology, 2018)
The aim of this study is to investigate current government measures to encourage Building Energy Efficiency (â€œBEEâ€) development in Indonesia. This study compiles and analyzes business models and financing options for retrofitting financing of BEE in Indonesia: establishing a framework for a critical comparative study, compare and assess the BEE government measures availability, and survey the customersâ€™ expectation of BEE measures. This study looks at the favorable measures that the Indonesian Government could take, and triangulate the findings of the comparative study and questionnaire survey to develop recommendations for BEE measures in Indonesia. It was found that the lack of economic incentives, diverse business models, and limited financing options might be the most prominent problems of the BEE promotion at the current stage in Indonesia. Un-consolidated policy among legislations is hampering the efforts of any BEE promotion. Tax incentives are likely to be more viable and efficient option for most of the Indonesian company, as well as active government interventions to promote BEE development. Illustrating the findings and regulatory analyses, as well as in-depth interviews with business representatives, this study identified several types of business models and some favorable financing option.Â Â